Identity crime and misuse in Australia: results of the 2013 online survey - Alice Hutchings
Abstract: Identity crime and misuse of personal information affect all sectors in Australia and cost individuals, business and government many millions of dollars annually. In May 2013, in order to explore the nature and scope of identity crime and misuse in Australia, the Australian Institute of Criminology was commissioned by the Attorney-General’s Department to undertake a national survey. This report presents the results of the survey. The findings confirm prior research that has found that identity crime affects a relatively high proportion of Australians who report substantial financial and other impacts